Basic accounting concepts and procedures : the why and wherefore approach to learning accounting - Garcia, Percy C. (Manila, 2006)
This book, conceived as the why and where-for approach to learning accounting, aims to introduce the beginner to the basic accounting concepts and procedures involved in processing business transactions of a sole proprietor engaged in the trading or merchandising business. The book is ideal as a textbook for a one semester six-unit course in basic accounting for business as well as accounting students. Professors can also benefit from well-organized topics to improve their presentations
Keywords: Accounting